PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS MENGGUNAKAN MODEL THINK PAIR SHARE DI KELAS V SD - Fajri, Haris; alwi, elma; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this research was improve the students achievement in learning social science make a Think Pair Share of 5 grade elementary school. Types of this   research   was   classroom   action   research   with   qualitative   and quantitative approach. Subject of this research were students of 5 grade were 22 people. Research conducted in two cycles with research procedure includes of planning, implementation, observation, and reflection. The result of research was improve a) Lesson plan the cycles of I was 87,5% and the cycles II of 96% b) Implementation  teacher’s  activity  of  I  cycle  was  79,65% and  II  cycle  was 95,8% while implementation students activity of I cycle was 76,6% and II cycle was 96,1% c) the students learning outcomes in the I cycle was 74,01 and  II  cycle  was 84,7 It  can be concluded  that make a Think Pair Share can improve students achievement in learning social science of 5 grade at SDN 27 Anak Air Kota Padang. Keyword : Learning outcomes, Social science, Think Pair Share